Membangun Kesadaran Hukum Dalam Menanggulangi Kenakalan Remaja Di Desa Setia Mekar Tambun Selatan - Bagas Dwi Saputra; Ahmad Baihaki; Nauval Hammam Fahlevi; Priska Laurensia (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
The role of law in society is to guarantee certaintyand justice, in In people's lives there are always differencesbetween patterns of behavior or the rules of behavior that applyin society with different patterns of behavior required by legalnorms. This can cause the emergence of a problem in the formof social inequality so that at a certain time tends to occurconflicts and social tensions which of course can interfere withthe course of social change in the desired direction. Building alaw-aware and law-abiding society is the goal of there arenorms that want a just society so that the joints of the culture ofsociety will develop towards the creation of a a social systemthat respects one another, makes people aware law and obey thelaw is not something that is easy by turning the palm hands,because not not everyone has legal awareness. Importancebuilding awareness and compliance with community law, it ishoped that it will support and make the community uphold theinstitutions/rules as fulfillment of the desire for obedience andlegal order. Role and the function of building legal awarenessand legal compliance is to: 1) Stability, 2) Providing a socialframework for internal needs society, 3) Providing a socialinstitutional framework in the form of norms, 4) Links betweeninstitutions. Law enforcement is the process of making efforts tothe establishment or functioning of legal norms as a guidelinebehavior in traffic or legal relations in life society and state.Because of that awareness of legal values and obedience incarrying out all the rules of law is a manifestation in effectingthe law.